Organizational happiness dimensions as a contribution to sustainable development goals: A prospective study in higher education institutions in Chile, Colombia and Spain (2020)
The aim of this study is to reveal the perception of current and future organizational happiness in the context of higher education institutions (HEIs) in a cross-national study, to reveal exploratory scenarios supporting the UN’s sustainable development goals (SDGs). Six dimensions of organizational happiness were considered for this study: Meaning, reliable relationships, positive emotions, engagement, achievement and recognition, and personal and professional development. To do so, Delphi methodology was used. An online survey was addressed to academics and support staff from three HEIs in different countries (Chile, Colombia and Spain), whose answers were analyzed using the Approximation of Qualitative Profiles mathematical technique. The results of this analysis show that there is a favorable prospective for happy workplaces, in all the dimensions for all countries. The implications of this research will serve HEIs’ human management practitioners to formulate effective policies for sustainable workplaces based on organizational happiness.